P-I-N 역구조 페로브스카이트 태양전지 응용을 위한 Nickel oxide 홀전달층의 열처리 온도 연구 - 김기성(Gisung Kim); 김미정(Mijoung Kim); 김효정(Hyojung Kim); 양정엽(JungYup Yang) (Current Photovoltaic Research, 2023)
A Nickel oxide (NiOx) thin films were prepared via sol-gel process on a transparent conductive oxide glass substrate. The NiOx thin films were spin-coated in ambient air and subsequently annealed for 30 minutes at temperatures ranging from 150℃ to 450℃. The structural and optical characteristics of the NiOx thin films annealed at various temperatures were measured using X-ray diffraction, field emission scanning electron microscopy, and ultraviolet-visible spectroscopy. After optimizing the NiOx coating conditions, perovskite solar cells were fabricated with p-i-n inverted structure, and its photovoltaic performance was evaluated. NiOx thin films annealed at 350℃ exhibited the most favorable characteristics as a hole transport layer, resulting in the highest power conversion efficiency of 17.88 % when fabricating inverted perovskite solar cells using this film.